Manufacturing platform of strategic innovation in global semiconductor industry. (1st January 2012) - Lin, Yu-Ling; Chu, Po-Yung
While integrated circuit (IC) companies in most countries are vertically integrated, Taiwan is an exception to that rule. An alternative business model for IC manufacturing was created out of and initiated by Taiwan's innovative foundry service strategy. A new IC ecosystem is clustered with platform leaders as well as constituent specialisation firms. Functioning as a whole and complementarily to one another, the separate but networked entities focus on their core business to create their own unique values. In the ecosystem, global IC design firms then emerge uniquely positioned. This platform also helps to explain the remarkable performance of small-medium enterprises (SMEs) in Taiwan's IC design segment.